-110=-5(7-3x)

Simple and best practice solution for -110=-5(7-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -110=-5(7-3x) equation:


Simplifying
-110 = -5(7 + -3x)
-110 = (7 * -5 + -3x * -5)
-110 = (-35 + 15x)

Solving
-110 = -35 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
-110 + -15x = -35 + 15x + -15x

Combine like terms: 15x + -15x = 0
-110 + -15x = -35 + 0
-110 + -15x = -35

Add '110' to each side of the equation.
-110 + 110 + -15x = -35 + 110

Combine like terms: -110 + 110 = 0
0 + -15x = -35 + 110
-15x = -35 + 110

Combine like terms: -35 + 110 = 75
-15x = 75

Divide each side by '-15'.
x = -5

Simplifying
x = -5

See similar equations:

| 5(t-4)=36 | | 4x^2+5x-6(x^2+x-2)= | | 5=20+r | | 10-x-1(-2)-8+4x= | | 16.7x=79.49 | | 3/5x-4=12 | | 4y=-9x | | 65/2 | | (y-7)(y-7)(y-7)=6 | | v+10=-1 | | 8316=(14784)r(9) | | 4x-6(2x-3)= | | -7+4m=-5+6m | | 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 |

Equations solver categories